Équations équilibrées la veille |
3 Sn(OH)3{-} + 2 Bi(OH)3 + 3 OH({-}) = 3 Sn(OH)6{-2} + 2 Bi
Na + Pb3(PO4)2 = Pb + Na3PO4 =>
6 Na + Pb3(PO4)2 = 3 Pb + 2 Na3PO4
Cs2 + H2 = CsH =>
Cs2 + H2 = 2 CsH
NO3{-} + H = NHO + H2O + e =>
NO3{-} + 5 H = NHO + 2 H2O + e
CH3COOC2H5 + O2 = CO2 + H2O =>
CH3COOC2H5 + 5 O2 = 4 CO2 + 4 H2O
Al + K2Cr2O7 + HSO4 = Al2(SO4)3 + Cr(SO4)3 + K2SO4 + H2O =>
14 Al + 3 K2Cr2O7 + 42 HSO4 = 7 Al2(SO4)3 + 6 Cr(SO4)3 + 3 K2SO4 + 21 H2O
Fe2S3(s) + HCl(g) = FeCl3(s) + H2S =>
Fe2S3(s) + 6 HCl(g) = 2 FeCl3(s) + 3 H2S
Fe(NO3)2 + Na2SO4 = FeSO4 + NaNO3 =>
Fe(NO3)2 + Na2SO4 = FeSO4 + 2 NaNO3
CaH2O2 + H3PO4 = Ca3(PO4)2 + H2O =>
3 CaH2O2 + 2 H3PO4 = Ca3(PO4)2 + 6 H2O
NaCl + Be = BeCl2 + Na =>
2 NaCl + Be = BeCl2 + 2 Na
C6H8O7 + NaCO3 = NaC6H8O7 + H2O + CO2 =>
10 C6H8O7 + 9 NaCO3 = 9 NaC6H8O7 + 4 H2O + 15 CO2
CH3CN + H2O = CH3CONH2 =>
CH3CN + H2O = CH3CONH2
HBr + NaOH = NaBr + H2O =>
HBr + NaOH = NaBr + H2O
HCO2CHCO2 + OH = CO2CHCO2 + H2O =>
HCO2CHCO2 + OH = CO2CHCO2 + H2O
PbI2 + Na(OH) = Pb(OH)2 + NaI =>
PbI2 + 2 Na(OH) = Pb(OH)2 + 2 NaI
Ni{+} = Ni + Ni{2+} =>
2 Ni{+} = Ni + Ni{2+}
CuO + P2O5 = Cu3(PO4)2 =>
3 CuO + P2O5 = Cu3(PO4)2
K2Cr2O7 + Ni + HNO3 = Cr(NO3)3 + Ni(NO3)2 + H2O + KNO3 =>
K2Cr2O7 + 3 Ni + 14 HNO3 = 2 Cr(NO3)3 + 3 Ni(NO3)2 + 7 H2O + 2 KNO3
Pb(OH)2 + Al2(CO3)3 = Al(OH)3 + PbCO3 =>
3 Pb(OH)2 + Al2(CO3)3 = 2 Al(OH)3 + 3 PbCO3
Na2O + SO2 = Na2SO3 =>
Na2O + SO2 = Na2SO3
NH4NO3 = (N2O)2 + H2O =>
2 NH4NO3 = (N2O)2 + 4 H2O
Pb(CH3COO)2 + OCl + H2O = PbO2 + Cl + CH3COOH =>
Pb(CH3COO)2 + OCl + H2O = PbO2 + Cl + 2 CH3COOH
O2 + I2 + H2O = HIO3 =>
5 O2 + 2 I2 + 2 H2O = 4 HIO3
Al2O3 + H2O = Al(OH)3 =>
Al2O3 + 3 H2O = 2 Al(OH)3
Zn + CO3 + HNO3 = Zn(NO3)2 + CO2 + H2O =>
Zn + CO3 + 2 HNO3 = Zn(NO3)2 + CO2 + H2O
Fe{3+} + (CO3){2-} = Fe2(CO3)3 =>
2 Fe{3+} + 3(CO3){2-} = Fe2(CO3)3
N2 + H3O = HN3 + H2O =>
3 N2 + 2 H3O = 2 HN3 + 2 H2O
Al2O3 + HCl = AlCl3 + H2O =>
Al2O3 + 6 HCl = 2 AlCl3 + 3 H2O
C6H10O + HNO3 = C6H10O4 + NO + H2O =>
C6H10O + 2 HNO3 = C6H10O4 + 2 NO + H2O
HCC + H2O = HCCH + OH =>
HCC + H2O = HCCH + OH
Mg + H2SO4 = MgSO4 + H2 =>
Mg + H2SO4 = MgSO4 + H2
SO2(g) + H2(g) = S(s) + H2O(g) =>
SO2(g) + 2 H2(g) = S(s) + 2 H2O(g)
MgCl2 = Mg + Cl2 = MgCl2 =>
MgCl2 = Mg + Cl2
CO + Cu = C + Cu2O =>
CO + 2 Cu = C + Cu2O
KMnO4 + HCl + CH3OH = MnCl2 + KCl + HCOOH + H2O =>
4 KMnO4 + 12 HCl + 5 CH3OH = 4 MnCl2 + 4 KCl + 5 HCOOH + 11 H2O
NaOH + KOOCC6H4COOH = KOOCC6H4COONa + H2O =>
NaOH + KOOCC6H4COOH = KOOCC6H4COONa + H2O